Learning to draw in Venice: the role of drawing manuals - Whistler, C (McGill-Queen's University Press, 2015)
A group of drawing manuals that were published in Venice in the early 1600s have taken on a high profile in the modern literature, being viewed as evidence of an impetus to reform Venetian disegno (drawing or design) by introducing Bolognese-inspired teaching methods. I argue that the concept of disegno in its tactile and abstract forms, as a practice and as an admirable element in art, was strongly rooted in 16th-century Venetian artistic culture. These manuals do not reflect a crisis in Venetian disegno, as is widely accepted in the scholarly literature. They were primarily aimed at aspiring virtuosi or art-lovers and collectors, and they attest to the increasing social value placed on the knowledge of drawing as a sign of gentility. The manuals were hybrid publications reflecting the new commercial possibilities of a growing virtuoso culture.